The Past and the Future of International Entrepreneurship: A Review and Suggestions for Developing the Field - Keupp, Marcus Matthias; Gassmann, Oliver (Journal of Management, 2009)
In this article, the authors analyze the field of international entrepreneurship (IE), which is in desperate need of further theory development. They study the field of IE since its inception by offering a comprehensive review of 179 articles on IE published in 16 journals over 14 years, covering the academic disciplines of strategic management, international business, entrepreneurship, and technology and innovation management. From a systematic content analysis of this literature, the authors develop an organizing framework to analyze the field's current status. On the basis of this analysis, the authors can identify theoretical inconsistencies, conflicting predictions, and knowledge gaps that all forestall the further development of IE research. They then develop directions for future research that can help to overcome these obstacles and promote future theory development.